2018
DOI: 10.1172/jci.insight.120757
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of immunological synapse-kinapse states reflects tumor escape to immunity in glioblastoma

Abstract: Since the proper activation of T cells requires the physical interaction with target cells through the formation of immunological synapses (IS), an alteration at this level could be a reason why tumors escape the immune response. As part of their life cycle, it is thought that T cells alternate between a static phase, the IS, and a dynamic phase, the immunological kinapse (IK), depending on high or low antigen sensing. Our investigation performed in tissue samples of human glioma shows that T cells are able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 51 publications
(61 reference statements)
1
9
0
2
Order By: Relevance
“…This actually challenges the conception of malfunctioning vessel wall and poor entry of immune cells in tumors [ 19 ], as T-cell adhesion and transmigration appear to be functional in GBM. This is actually consistent with previous results from our group, in which we showed that T cells enter the GBM parenchyma as nonproductive lymphocytes in a patrolling mode, displaying a kinaptic state, which entails increased motility and random walking within the tumor [ 5 ]. At least for GBM, the BTB does not seem to hamper immune cell infiltration.…”
Section: Discussionsupporting
confidence: 93%
“…This actually challenges the conception of malfunctioning vessel wall and poor entry of immune cells in tumors [ 19 ], as T-cell adhesion and transmigration appear to be functional in GBM. This is actually consistent with previous results from our group, in which we showed that T cells enter the GBM parenchyma as nonproductive lymphocytes in a patrolling mode, displaying a kinaptic state, which entails increased motility and random walking within the tumor [ 5 ]. At least for GBM, the BTB does not seem to hamper immune cell infiltration.…”
Section: Discussionsupporting
confidence: 93%
“…Glioma cells are another example in which disease progression is correlated with a decrease in cellular stiffness ( Pepin et al, 2018 ). Intriguingly, glioblastoma cells evade T-cell killing by locally preventing IS formation, with interactions characterised by kinapse dynamics ( Díaz et al, 2018 ). There are settings in which it may be preferential for an NK cell not to form a full IS, with a kinapse-like mode of interaction allowing deeper penetration into solid tumours ( Deguine et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Human biopsies stained by immunofluorescence were imaged with a confocal laser-scanning microscope (LSM 700, Carl Zeiss, Oberkochen, Germany) utilizing a Plan-Apochromat 40×/1, 3 Oil DIC M27 objective lens (Carl Zeiss) and processed with the ZEN 2010 software (Carl Zeiss). Three-dimensional reconstructions were generated using the α blending softwares ZEN 2010, Imaris (BitPlane, South Windsor, USA) and iLlucida FX (iLlucida LLC, Los Angeles, USA) as we recently described ( Diaz et al , 2018 ). Z-stacks in the regions of interest were acquired to cover the depth of the tissue (25–30 images/stack) with a 0.5–μm-step size, and the images for quantification were always taken with the NF on the upper part of the image, considering that the scanning field could be rotated and oriented.…”
Section: Methodsmentioning
confidence: 99%